Incentives for Conservation and Quality-Improvement by Public Utilities - Lewis, Tracy R.; David E. M. Sappington (American Economic Review, 1992)
We examine the design of incentive programs to motivate regulated utilities to supply both basic service (e.g., electricity supply, local telephone service) and service enhancements (e.g., energy-conservation services, improved clarity and speed of voice communication). The optimal regulatory programs are shown to vary greatly, depending upon the information available to the regulator. The price of the basic service may optimally be distorted above or below marginal cost to better motivate the supply of the service enhancement. Our policy prescriptions are compared with current programs and proposals to promote energy conservation.